Comparison of the activity of short stay independent hospitals in England and Wales, 1981 and 1986. Issue 6668 (28th January 1989) - Nicholl, J. P.; Beeby, N. R.; Williams, B. T.
Abstract : From a sample of 19, 000 treatment episodes at 183 of the 193 independent hospitals with operating facilities in England and Wales that were open during 1986 it is estimated that 404, 000 inpatients were treated in 1986 (an increase of 48% since 1981) and 99, 000 day cases (an increase of 112%). It was found that the procedure most commonly performed was abortion, though this made up only 19% of the total caseload in 1986 compared with 30% in 1981, otherwise the case mix in 1986 was similar to that in 1981. Fewer patients came from overseas in 1986 than in 1981, but the distribution by age and sex remained the same, with three quarters of the patients aged between 15 and 65. The estimated bed occupancy in the independent hospitals in 1986 was less than 60% nationally and only 52% in the Thames regions. It is concluded that in these five years the nature of the independent hospital sector changed little, and in 1986 the activity still consisted largely of routine cold elective surgery for people of working age, and the regional differences in admission rates to independent hospitals were nearly as great as in 1981.